New record of the poorly known lizard Enyalius capetinga (Squamata: Leiosauridae) from the Brazilian Cerrado - Maffei, Fabio [UNESP]; Nascimento, Bruno Tayar Marinho do [UNESP] (Inst Ciencias Naturales, Museo Historia Natural, 2023)
The lizard Enyalius capetinga is the most recently described species of the genus and is endemic to the Cerrado biome of central Brazil. Here we present a new record for this species from the Municipality of Estrela do Sul, in the state of Minas Gerais, Brazil. This finding fills a 110-km gap in the distribution of the species and is just the eighth reported locality for the species range-wide.
Keywords: Brasil; distribuci & oacute;n geogr & aacute;fica; Minas Gerais; Reptilia; savana